ANALISIS RETURN ON ASSET (ROA), QUICK RATIO (QR), UKURAN PERUSAHAAN,KUALITAS AUDIT, DAN OPINI AUDIT TAHUN SEBELUMNYA TERHADAP OPINI AUDIT DENGAN ASUMSI GOING CONCERN PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG LISTING DI BEI - Wulan Desriza Putri; Rita Anugerah; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study is to analyze the influence caused by return on assets, quick ratio, firm size, audit quality, and previous year audit opinion against audit opinion with going concern assumption. By using descriptive quantitative study that reveal the value of an influence or relationships between variables that stated in number, by collecting data which is a supporting factor for influence between the variables in question and then analyzed using analysis tools in accordance with the variables in the study (Subagyo, 2005:84). From the results of this study it's concluded that the return on assets and the previous year's audit opinion has a significant level that is under 0.05, which means that these variables affect the audit opinion with a going concern assumption. For quick ratio variables, firm size and audit quality does not significantly affect the audit opinion with a going concern assumption.Keywords: Return on assets, quick ratio, firm size, audit quality, and going concern assumption.